Thermoregulation of competitive artistic gymnastic athletes and non-athlete girls exercising in the heat - Gabriela Tomedi Leites; Paulo Lague Sehl; Giovani dos Santos Cunha; Adriano Detoni Filho; Flavia Meyer (Universidade Federal de Santa Catarina, 2016)
It's unclear whether the combination of intense, chronic training and heat exposure during prepubescence improves thermoregulatory responses to exercise in artistic gymnastics athletes. The objective of this study was to compare thermoregulatory and perceptual responses between artistic gymnastics athletes and non-athlete girls while exercising both in heat and thermoneutral conditions. Seven athletes (8.7 ± 1.3 yrs) and 7 nonathletes (9.4 ± 1.5 yrs) cycled for 30 min at load (W) of ~55% VO2peak, on two separate occasions in a randomized order: heat (35˚C, 40% relative humidity) and thermoneutral conditions (24˚C, 50% relative humidity). Rectal temperature, heart rate, rate of perceived exertion, thermal sensation, thermal comfort and irritability were measured throughout the exercise. Initial rectal temperature was similar between athletes and non-athletes in both heat (37.2 ± 0.4 vs. 37.4 ± 0.2˚C, respectively) and thermoneutral conditions (37.3 ± 0.2 vs. 37.3 ± 0.3˚C). Final rectal temperature was similar between groups (38.0 ± 0.2 vs. 38.2 ± 0.2˚C in heat and 37.8 ± 0.2 vs. 37.9 ± 0.2˚C in thermoneutral conditions). Initial heart rate was lower in athletes in the heat (76 ± 7 vs. 91 ± 11 bpm, P = 0.01); however, throughout cycling, it became similar between groups. Athletes reported similar perceptual responses compared to non-athletes, with the exception of higher thermal comfort in the 10th minute of exercise in thermoneutral conditions (P = 0.003). It was concluded that athletes were similar to non-athletes with respect to thermoregulatory and perceptual responses during 30 min of cycling at similar relative intensities.